The Effect of Improvisation Technique towards EFL Students’ Speaking Ability - Hadeli Hadeli; Eviani Eviani (AT-TA'LIM, 2017)
The purpose of this research was to determine whether Improvisation Technique gave significant difference in teaching transactional and interpersonal conversation text toward students’ speaking ability. This research was also aimed to find out which components of students’ speaking were mostly improved after using Improvisation Technique. True experimental research was used where the sample was chosen by using cluster random sampling. The result of this research showed that the students had made some progresses. It showed that the mean score of students’ speaking ability in experimental class (79.50) was higher than the mean score of students’ speaking ability in control class (72.21). It means that teaching speaking by using Improvisation Technique gives significant effect towards students’ speaking ability. Based on the research finding, it can be concluded that using Improvisation Technique gave significant effect towards students’ speaking ability at class XI of Senior High School 12 Padang. Thus, it is recommended for English teacher should consider the use of Improvisation Technique as an alternative technique in teaching speaking for getting significant effect towards students’ speaking ability.